Bike boys, drag queens & superstars : avant-garde, mass culture, and gay identities in the 1960s underground cinema - Suárez, Juan Antonio (Indiana University Press, 1996)
At the confluence of experimental art and the gay subculture of early 1960s New York, Juan Suárez discovers a postmodern, gay-influenced aesthetic that "recycles" popular culture. Filmmakers Kenneth Anger, Jack Smith, and Andy Warhol epitomize this sensibility, combining the influences of European avant-garde movements, comic books, rock 'n' roll, camp, film cults, drag performances, fashion, and urban street cultures.